2003
DOI: 10.1097/01.brs.0000059762.89308.97
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Rofecoxib in Patients with Chronic Low Back Pain

Abstract: Rofecoxib significantly reduced chronic low back pain in adults and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…The efficacy of prescribed anti-inflammatories, namely COX-2 selective inhibitors, in treating NeP hyper-inflammation remains unexplored. Existing research only demonstrated improved patient-reported outcomes for NoP cases [ [6] , [7] , [8] ]. This study demonstrated equivalent efficacy in patients taking prescribed anti-inflammatories for NeP and NoP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of prescribed anti-inflammatories, namely COX-2 selective inhibitors, in treating NeP hyper-inflammation remains unexplored. Existing research only demonstrated improved patient-reported outcomes for NoP cases [ [6] , [7] , [8] ]. This study demonstrated equivalent efficacy in patients taking prescribed anti-inflammatories for NeP and NoP.…”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol (acetaminophen) and non-steroid anti-inflammatory drugs (NSAIDs) have anti-pyrectic and analgesic actions. Studies have only shown NSAIDs and paracetamol to be effective in patients with chronic LBP without sciatica and NeP signs [ [6] , [7] , [8] ]. The positioning of neuromodulating agents and opioids, is heavily debated by national and international guidelines in treating chronic LBP.…”
Section: Introductionmentioning
confidence: 99%
“…При хронической неспецифической ПБ в сравнении с плацебо изучались напроксен [50], эторикоксиб [51], валь-декоксиб [52] и рофекоксиб [53]. Показана эффективность различных НПВП в отношении уменьшения боли, повышения функциональной активности, улучшения физического КЖ; не установлено преимущество какого-либо определенного НПВП перед другими [12,54].…”
Section: лекарственная терапияunclassified
“…Effective therapies from drugs to surgery for CNLBP are widely used ( Ma et al, 2019 ). NSAIDs, such as Celecoxib and other COX-2 inhibitors are frequently advised for the treatment of CNLBP ( Birbara et al, 2003 ; Katz et al, 2003 ; Pallay et al, 2004 ; Airaksinen et al, 2006 ). The effectiveness of exercise therapy in CNLBP, including pilates, Tai Chi, yoga, and motor control exercise (MCE), has received greater attention in recent years ( van Middelkoop et al, 2011 ; Holtzman and Beggs, 2013 ; Macedo et al, 2013 ; Eliks et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%